Realização de técnicas estendidas em três obras selecionadas do repertório brasileiro para piano solo do século XXI: apresentação e discussão - Oliveira, Jonathan Taylor de (2014)
This work discusses the performance of the extended techniques found in three Brazilian pieces for solo piano composed in the 21st Century in light of this researcher’s musical upbringing, which did not include repertoire with extended techniques. The pieces selected are Pó (2008), by Liduino Pitombeira (1962- ), Prélude VII (2008), by Marcílio Onofre (1982), and Pianimbau (2011), by Daniel Wolff (1968). The criteria for selecting the pieces were a contrasting compositional language between the pieces and that they should not be for beginner or intermediate levels. These pieces were the object of both parts of this research: Part A, in which the pieces were studied and prepared for the final recital, and Part B, which consists of a written record of the research. The historical context of the extended techniques found in the selected pieces, based on authors such as Stone (1980), Costa (2004), Burge (2004) and Ishii (2005), guided the investigation of the technical and interpretative aspects of the pieces. The discussions dealt with the following topics: type of extended technique, notation, dynamics, region of the piano on which a technique is performed, ways to perform a technique, parts of the body that are used, physical structure of the piano, materials used, and the sound resulting from the use of a technique. The research that was undertaken made it possible to conclude that the performance of these techniques within the established parameters involved the adaptation of technical abilities acquired previously during this researcher’s musical upbringing, as well as the development of new abilities. This research also revealed that extended techniques are present in the piano repertoire written by present day Brazilian composers, and it is thus pertinent to study such pieces throughout one’s musical upbringing.